Facilitating All‐Inorganic Halide Perovskites Fabrication in Confined‐Space Deposition. Issue 7 (6th April 2020) - Wang, Renyan; Muhammad, Yasar; Xu, Xiang; Ran, Meng; Zhang, Qingfu; Zhong, Junchuan; Zhuge, Fuwei; Li, Huiqiao; Gan, Lin; Zhai, Tianyou
Abstract: 2D all‐inorganic halide perovskites (2D AIHP) have attracted huge attention for their excellent optoelectronic properties and superior atmospheric stability for organic–inorganic halide perovskites. 2D AIHP has been fabricated by varied strategies, whereas a satisfied way to simultaneously reach good quality, dimensions, and uniformity is still far from achieved yet. Here, a direct thermal deposition method to synthesize 2D AIHP of lateral length up to ≈30 µm and uniform thickness down to ≈10 nm, which shows excellent optoelectronic performance comparable to the reported top‐level 2D AIHP, is proposed. A vertical mass transport instead of conventional horizontal mode is adopted, significantly enhancing the deposition stability. Furthermore, the morphologies of AIHP are switchable between nanowires and nanoflakes under the control of deposition temperature. This method may pave the way for uniform fabrication of 2D AIHP or AIHP‐based 2D heterostructures for various applications. Abstract : Achieving uniform all‐inorganic halide perovskites (AIHP) with large size and ultrathin thickness simultaneously is a challenge. A novel deposition strategy is proposed where AIHP grows in a confined space to significantly enhance the growth stability. AIHP of ≈30 µm lateral length and ≈10 nm thickness are fabricated, showing high quality comparable to the reported top‐level AIHP.